In-vitro evaluation of biphasic calcium phosphate/casein incorporated with Myristica fragrans for bone tissue engineering. Issue 1 (January 2015) - Kumar, B. Santhosh; Muthukumar, T.; Deepachitra, R.; Charumathy, R.K.; Hemalatha, T.; Sastry, T.P.
Abstract: Plant extracts are used in medicine due to their effectiveness, fewer side effects and low cost. In the present study, bone graft containing bioactive biphasic calcium phosphate (BCP), biocompatible casein (C), and the extract of Myristica fragrans (MF) was prepared. These bone grafts were characterized using Fourier transform infrared spectroscopy, thermogravimetric analysis, X-ray diffraction, and scanning electron microscope techniques. Incorporation of Casein (C) and M. fragrans (MF) decreased the porosity and enhanced the mechanical properties of the bone grafts. The biomimetic mineralization capacity of BCPC–MF implant was evaluated in simulated body fluid solution for 21 days. The results revealed that, BCPC–MF implant has shown better compression strength compared to that of BCP. BCPC–MF implant has shown enhanced proliferation and induced alkaline phosphatase activity in NIH-3T3, MG-63 and SaOS-2 cell lines, compared to BCP. Since, the in vitro results of BCPC–MF as bone graft material is promising, further studies are being carried out in experimental animal models.